If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 10y = 15y + 3 Reorder the terms: -12 + 10y = 3 + 15y Solving -12 + 10y = 3 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. -12 + 10y + -15y = 3 + 15y + -15y Combine like terms: 10y + -15y = -5y -12 + -5y = 3 + 15y + -15y Combine like terms: 15y + -15y = 0 -12 + -5y = 3 + 0 -12 + -5y = 3 Add '12' to each side of the equation. -12 + 12 + -5y = 3 + 12 Combine like terms: -12 + 12 = 0 0 + -5y = 3 + 12 -5y = 3 + 12 Combine like terms: 3 + 12 = 15 -5y = 15 Divide each side by '-5'. y = -3 Simplifying y = -3
| 390=30*3+42h+195 | | x-(-6)=20 | | x-.1x=27.76 | | 9n+8=71 | | 96-28*x=-x^2 | | -3y+2= | | 5n-15=15 | | 96-28x=x^2 | | ln(x+1)=ln(3x+3) | | -2(4-3*0.7)= | | 4x^3+3x^2-2=0 | | p-0.1=1.4 | | -2(4-3y)=3+9(y-1) | | x=.8x+100 | | 2+5(x-2)=7 | | 4x+1.1-1.2x=0.3x-2.4 | | 7+b=-5 | | 0=m-15 | | 3w=69 | | 4k-12=4 | | 9x+11-4x=12-13x-14 | | c=200+0.75(y+100) | | 4u=56 | | 21=4x-15 | | 2x=44 | | 21=4x-5 | | 3v=69 | | y=5x+1400 | | 1+5=14 | | 9x+10=4x+10 | | 5-4=y | | a-3=12 |